Phytochemical screening and biological activities of pakoba (Syzygium luzonense) stem bark ethanol extract - Mario Walean; ROSTINA MELPIN; MERVINA RONDONUWU; KINZIE FELICIANO PINONTOAN; Hendra Pratama Maliangkay; MELI ASTRIANI (Society for Indonesian Biodiversity, 2020)
Abstract. Walean M, Melpin R, Rondonuwu M, Pinontoan KF, Maliangkay HP, Astriani M. 2020. Phytochemical screening and biological activities of pakoba (Syzygium luzonense) stem bark ethanol extract. Biodiversitas 21: 2377-2382. Pakoba (Syzygium luzonense (Merr.) Merr) as an endemic and ethnomedical plant of North Sulawesi was investigated for its phytochemical constituents and biological activities. The presence of phytochemicals constituents, antibacterial, antioxidant activities, and antihyperglycemic of pakoba stem bark ethanolic extract (PSBEE) were also investigated. Pakoba stem bark was extracted using ethanol. The extracts were evaluated for antimicrobial activity using the Kirby Bauer method, whereas antioxidant activity was determined by using 1,1-diphenyl-2-picrylhydrazyl radical scavenging assay. Alloxan-induced diabetic rats investigation was used to determine the antihyperglycemic activity. The phytochemical analysis revealed that tannins, alkaloids, and flavonoids were present in PSBEE. PSBEE has potent antioxidant activity with antioxidant activity index = 1.02. PSBEE significantly reduced the blood sugar of hyperglycemic rats with an optimum dose of 300 mg/kgbw. In this study, PSBEE has weak antibacterial activity against in Escherichia coli and Staphylococcus aureus.